Resistance to KRAS inhibition in advanced non-small cell lung cancer - Sreter, Katherina Bernadette; Catarata, Maria Joana; von Laffert, Maximilian; Frille, Armin (Frontiers in Oncology, 2024)
Lung cancer remains the leading cause of cancer death globally. More than 50% of new cases are diagnosed in an advanced or metastatic stage, thus contributing to the poor survival of such patients. Mutations in the KRAS (Kirsten rat sarcoma virus) gene occur in nearly a third of lung adenocarcinoma and have for decades been deemed an 'undruggable' target. Yet, in recent years, a growing number of small molecules, such as the GTPase inhibitors, has been investigated in clinical trials of lung cancer patients harboring KRAS mutations, yielding promising results with improved outcomes. Currently, there are only two approved targeted therapies (adagrasib and sotorasib) for advanced or metastatic KRAS-mutated NSCLC from the second-line setting onwards. In this narrative review, we will focus on KRAS, its molecular basis, the role of its co-mutations, clinical evidence for its inhibition, putative mutation to resistance, and future strategies to overcome resistance to KRAS inhibition.